2014
DOI: 10.7314/apjcp.2014.15.7.3001
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Annexin A3 in Gastric Cancer and its Correlation with Proliferation and Apoptosis

Abstract: Annexin A3 has been identified as a novel biomarker in different types of cancers. However, little is known about its clinical significances and and biological roles in gastric cancer. In this study, we assessed annexin A3 expression in 80 patients with gastric cancer and explore its correlation with prognosis Moreover, correlations with Ki-67, Bcl-2 and Bax were also investigated. Expression of annexin A3 was increased in gastric cancer compared with that in normal gastric tissues. Annexin A3 expression was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Furthermore, the tumors of nude mice of the shAnxa3 group showed reduced Ki-67 expression compared with that in mice of the control group, suggesting that Anxa3 affects cell proliferation in LADC. Moreover, the expression of Anxa3 was reported to be positively correlated with Ki-67 expression in gastric cancer [11]. All of the above results indicated that Anxa3 plays a vital role in cancer cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the tumors of nude mice of the shAnxa3 group showed reduced Ki-67 expression compared with that in mice of the control group, suggesting that Anxa3 affects cell proliferation in LADC. Moreover, the expression of Anxa3 was reported to be positively correlated with Ki-67 expression in gastric cancer [11]. All of the above results indicated that Anxa3 plays a vital role in cancer cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Anxa3 might function as either a tumor promoter or suppressor in different cancers [7, 8]. As found, the upregulation of Anxa3 expression could promote the development of colorectal cancer and gastric cancer [911] and enhance the metastatic activity of LADC [12]. However, in prostatic cancer and renal cancer, it was shown that there is a relationship between Anxa3 downregulation and tumor cells development [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have reported that knockdown of ANXA3 reduces growth of lung adenocarcinoma, breast, and gastric cancer cells . ANXA3 is inversely related to prognoses of patients with gastric cancer, and it positively regulates the expression of Bcl‐2 . ANXA3 knockdown inhibits cell proliferation and facilitates apoptosis in breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…It has three different domain composition: a short The C-terminus domain including four conserved ‘annexin repeat’ domains I, II, III and IV, a repeated collagen-like sequence, and a COOH-terminal domain including a single carbohydrate recognition-binding domain [1415]. It is a membrane associated protein involved in the regulation of varieties of biological responses, containing cell proliferation, angiogenesis, cancer progression and metastasis [1618]. ANXA3has been identified as a putative tumor oncogene in a diversity of carcinomas, such as Ovarian carcinoma, Lung adenocarcinoma, hepatocellular carcinoma, Colorectal cancer [1922].…”
Section: Introductionmentioning
confidence: 99%